2013
DOI: 10.1002/ccd.24524
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanism of annulus rupture during transcatheter aortic valve implantation

Abstract: Although annulus rupture is one of the most severe complications of transcatheter aortic valve implantation (TAVI), the incidence and mechanism of this complication remain unclear. Out of 387 consecutive TAVI cases in our institution, the incidence of annulus rupture was 1.0% (4/387). The first two patients died because of hemodynamic collapse due to tamponade on day 0. Both surviving patients had undergone preprocedural multidetector computed tomography which revealed large calcifications in the epicardial fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 3 publications
1
49
0
1
Order By: Relevance
“…Recently, Hayashida et al showed that significant calcification located in a vulnerable area as revealed by MDCT might be a possible mechanism for annular rupture in 2 cases of balloon-expandable TAVR. 17 Some have suggested that the location of LVOT calcification might also increase the risk of annular rupture. Theoretically, trigonal calcification may impart greater rigidity to the annulus and make it prone to rupture, whereas more anterior calcification may not impart as great of a risk.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hayashida et al showed that significant calcification located in a vulnerable area as revealed by MDCT might be a possible mechanism for annular rupture in 2 cases of balloon-expandable TAVR. 17 Some have suggested that the location of LVOT calcification might also increase the risk of annular rupture. Theoretically, trigonal calcification may impart greater rigidity to the annulus and make it prone to rupture, whereas more anterior calcification may not impart as great of a risk.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly the case for the inflow portion of the valve as this is the site where most of the complications occur, for example paravalvular regurgitation and bundle branch block and also the rare but dramatic event of coronary obstruction [7][8][9][10][11][12][13] . Most likely, the overestimation unveils limitations of the software.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the latter, one might cite as examples incomplete and/or non-circular frame expansion due to the presence of aortic root calcifications leading to paravalvular regurgitation, unexpected mobilisation of calcified leaflets leading to coronary obstruction, and dissection or rupture of the aortic root even in the presence of appropriate valve size selection [7][8][9][10][11][12][13] . Device-host interactions are clinically difficult to predict because of the large variations in the geometry and dimensions of the aortic root in addition to the variations in the amount and distribution of calcium between patients.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 3; [17,18]), severe asymmetric subvalvular hypertrophy, and global left ventricular hypertrophy in the elderly, especially in female patients with relatively weak myocardium.…”
Section: Aortic Annulus Rupturementioning
confidence: 99%